Formulation of Antiaging Activities in Creams Made From Natural Active Ingredients - Maria Chatarina Indiradewi Hastiningsih (Sean Institute, 2024)
Anti-aging treatments have become a major focus in the beauty industry, with anti-aging creams being one of the most sought after products to treat the signs of skin aging. This cream is formulated with the aim of inhibiting the premature aging process, reducing the appearance of wrinkles, and disguise skin imperfections. Natural ingredients with antioxidant activity have been in the spotlight in the development of anti-aging cream formulations, due to their ability to fight skin damage caused by free radicals. In an effort to identify effective cream formulations, the literature review method was used to evaluate various relevant reference sources. This literature review revealed several natural ingredients that have anti-aging potential, such as tamarind leaf extract, banana peel, purple eggplant, and moringa leaves, as well as ylang-ylang oil and lemon oil. In addition, fruits such as rambutan and lemon, as well as red spinach leaves, also stand out for their high antioxidant content, including vitamin C and lycopene. This research provides insight into the various natural ingredients that can be used in anti-aging cream formulations, leading to the development of more effective and environmentally friendly products in caring for skin.